Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Toko Oleh-Oleh Christine Hakim Kota Padang - Alvin Novri Weli; Tiara Turay (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect of price and service quality on customer satisfaction at Christine Hakim Souvenir Shop in Padang City. This research employs a quantitative approach with a survey method. The population consists of all customers of Christine Hakim Shop, with a sample of 150 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using validity and reliability tests, multiple linear regression, t-test, and F-test. The results indicate that (1) price has a significant effect on customer satisfaction, (2) service quality has a significant effect on customer satisfaction, and (3) price and service quality simultaneously have a significant effect on customer satisfaction. Therefore, it can be concluded that an appropriate pricing strategy and improvement in service quality play an essential role in creating customer satisfaction at Christine Hakim Souvenir Shop in Padang City.